LITERATURE ANALYSIS OF CHOLESTEROL LEVEL DETERMINATION VIEWS AND STEPS - Yaminova N.Kh (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
In this article, the manifestations of cholesterol levels in the population of the world, stages, as well as risk factors and comorbidity, formed and developed myocardial infarction, diagnosis of its non-traditional types, use of modern methods used in epidemiology, prediction and prevention, its antecedent condition, theoretical basis of the systematic procedure for early diagnosis of complication processes are presented in this article. explained by its creation. Also, the results obtained during the research were analyzed in depth. The results of the analysis are presented during the coverage of the topic.